Costa Rica: Global Competitiveness and Higher Education. Results for 2008–2010 - Aguilar Fernández, Eduardo (2011)
The Global Competitiveness Index expresses in numerical terms the country`scompetitiveness. the index to group 12 pillars of competitiveness, one of these is higher education and training. Respect to Costa Rica, this pillar show a very important advantages respect to other countries: Chile, Panama and Mexico; nevertheless, is necessary to better other aspects in higher education for further balance growth.